2021
DOI: 10.3390/pr9050870
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Hydrodynamics of Taylor Flow in Microchannels: Experimental and Computational Studies

Abstract: Taylor flow is a strategy-aimed flow to transfer conventional single-phase into a more efficient two-phase flow resulting in an enhanced momentum/heat/mass transfer rate, as well as a multitude of other advantages. To date, Taylor flow has focused on the processes involving gas–liquid and liquid–liquid two-phase systems in microchannels over a wide range of applications in biomedical, pharmaceutical, industrial, and commercial sectors. Appropriately micro-structured design is, therefore, a key consideration fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 185 publications
0
19
0
Order By: Relevance
“…Recently, a comprehensive review on the hydrodynamics of Taylor flow through mini‐ and microchannels was published. [ 94 ] It shows the dependency of slug length on the properties of phases, volumetric flow rate ratio, gas holdup, and non‐dimensional numbers.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a comprehensive review on the hydrodynamics of Taylor flow through mini‐ and microchannels was published. [ 94 ] It shows the dependency of slug length on the properties of phases, volumetric flow rate ratio, gas holdup, and non‐dimensional numbers.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the hydrodynamics forms the basis for reaction/mass transfer inside the microchannels. Several experimental and simulation studies were conducted to investigate the hydrodynamics of multiphase flows (gas–liquid, liquid–liquid, gas–liquid–liquid) in a single microchannel. It was reported that hydrodynamic parameters such as the formation/coalescence of droplets/bubbles/slugs and their respective lengths and flow patterns in a single microchannel were strongly dependent on the micro-/millichannel design, operating parameters, and fluid properties. However, numbering-up to the thousands of parallel channels required to match the industrial production scale throughput has many challenges.…”
Section: Introductionmentioning
confidence: 99%
“…It may lead to a decrease in the heat and mass transfer coefficient despite the inherent benefits of MSR. It should be noted that the significant factors that affect the maldistribution are channel geometry (size, shape, and aspect ratio), fluid distributors (T or Y), and fluid properties (density and viscosity of phases). ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas slugs are used in mass transfer limited reactions, drug delivery and other pharmaceutical operations in Lab-on-chip devices [18]. Previous studies focusing on combining gas slugs with acoustic streaming, have analysed applications in particles separation [9] and micromixing [19].…”
Section: Introductionmentioning
confidence: 99%